Ecology of Political Communication of Acehnese People towards 2024 Local Election - Zulham; Ristati (CV. Literasi Indonesia, 2021)
The local election is a political and democratic tool owned by the community after Indonesia's reformation. Aceh and its regencies and cities will carry out the local election in 2022. The central government's policy to postpone the implementation of the local election in 2024 has created a polemic in the community. Based on this phenomenon, this study aims to determine the problems that arise in political communication among the community against the central government's unilateral policy in delaying the implementation of the local election. The approach used was qualitative by using observation and interview techniques. The results of this study are: The Acehnese are disappointed with the central government's intervention in the form of a policy of postponing the local election, based on the justification that Aceh has the local regulation, that is called 2006 Aceh Government Law, where Aceh has independence in managing its household. Furthermore, the communication built by the Central Government is coercive communication, ignoring comprehensive communication from the community. With the ecological influence of the local election postponement policy and communication built by the central government, the people ignore the government's advice to keep the environment more conservative and ignore the fight against Covid-19.